2015
DOI: 10.1159/000431324
|View full text |Cite
|
Sign up to set email alerts
|

Novel Heterozygous Mutations of <b><i>NR5A1</i></b> and Their Functional Characteristics in Patients with 46,XY Disorders of Sex Development without Adrenal Insufficiency

Abstract: Background/Aims: Heterozygous mutations of NR5A1, which encodes steroidogenic factor 1 (SF1), were identified in patients with 46,XY disorders of sex development (DSD) with normal adrenal function. This study was aimed to identify and functionally characterize mutations of NR5A1 in patients with 46,XY DSD. Methods: This study included 51 patients from 49 unrelated families with 46,XY DSD. Genomic DNA was extracted from peripheral blood leukocytes, and direct sequencing of all coding exons and their flanking in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 31 publications
0
15
1
Order By: Relevance
“…This variant was not present in any of the 60,706 exomes in ExAC. A nearly identical frameshift variant, c.1151del, p.Leu384Argfs*7, was recently reported in a 46,XY female with clitoromegaly and was shown to have significantly decreased activity of the protein product SF-1 on functional assays[20]. Sequencing of Subject One’s parents revealed the same variant in the subject’s father.…”
Section: Resultsmentioning
confidence: 75%
“…This variant was not present in any of the 60,706 exomes in ExAC. A nearly identical frameshift variant, c.1151del, p.Leu384Argfs*7, was recently reported in a 46,XY female with clitoromegaly and was shown to have significantly decreased activity of the protein product SF-1 on functional assays[20]. Sequencing of Subject One’s parents revealed the same variant in the subject’s father.…”
Section: Resultsmentioning
confidence: 75%
“…This initial patient bearing the heterozygous p.Gly35Glu mutation presented with adrenal failure and gonadal dysgenesis with persistent Mullerian derivatives (Woo et al, 2015), a phenotype that closely resembled the phenotype observed in murine Nr5a1 knockout models (Luo et al, 1994). Gonadal dysgenesis and adrenal insufficiency were also present in the second reported NR5A1‐related 46,XY DSD, in a patient bearing the homozygous p.Arg92Gln mutation (Achermann et al, 2002).…”
Section: Discussionmentioning
confidence: 72%
“…More than 80 different NR5A1 variants, distributed across the full length of the protein, have been described and the majority are nonsynonymous mutations (Pedace et al, 2014; Tantawy et al, 2014; Woo et al, 2015; Fabbri et al, 2016). Most of these mutations are located in the DBD and are in a heterozygous state or compound heterozygous state with the p.Gly146Ala (rs1110061) variant, with the exception of two mild mutations described in homozygous state (Achermann et al, 2002; Soardi et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are consistent with prior observations that identical NR5A1 mutations can be associated with broad phenotypic variations. 8,10,11 Indeed, C-terminal mutations of NR5A1 have been shown to cause 46,XY DSD of various clinical severities without any genotype–phenotype correlations (Supplementary Figure S1). 4–8 Our case provides an additional example of the intrafamilial phenotypic variation of NR5A1 abnormalities.…”
mentioning
confidence: 99%